CRACK-JUMP MECHANISM AND ITS IMPLICATIONS FOR STRESS CYCLICITY DURING EXTENSION FRACTURING - Caputo R.; Hancock P.L. (My University, 1999)
It is well accepted and documented that faulting is produced by the cyclic behaviour of a stress field. Some extension fractures, such as veins characterised by the crack-seal mechanism, have also been presumed to result from repeated stress cycles. In the present note, some commonly observed field phenomena and relationships such as hackle marks and vein and joint spacing, are employed to argue that a stress field can also display cyclic behaviour during extensional fracturing. Indeed, the requirement of critical stress conditions for the occurrence of extensional failure events does not accord with the presence of contemporaneously open nearby parallel fractures. Therefore, because after each fracture event there is stress release within the surrounding volume of rock, high density sets of parallel extensional fractures also strongly support the idea that rocks undergo stress cyclicity during jointing and veining. A comparison with seismological data from earthquakes with dipole mechanical solutions, confirms that this process presently occurs at depth in the Earth crust.Furthermore, in order to explain dense sets of hair-like closely spaced microveins, a crack-jump mechanism is introduced here as an alternative to the crack-seal mechanism. We also propose that as a consequence of medium-scale stress cyclicity during brittle deformation, the re-fracturing of a rock mass occurs in either one or the other of these two possible ways depending on the ratio between the elastic parameters of the sealing material and those of the host rock. The crack-jump mechanism occurs when the former is stronger.